Công văn số 1645/BNV-TCBC ngày 14/4/2016 của Bộ Nội vụ báo cáo tình hình thực hiện tinh giản biên chế. - Bộ Nội Vụ (2016)
Nội dung Công văn số 1645/BNV-TCBC ngày 14/4/2016 của Bộ Nội vụ báo cáo tình hình thực hiện tinh giản biên chế.